Problem Based Learning in Basic Education - Eka Nur Samsudin; Murniningsih Murniningsih; Ali Mustadi (AL-ISHLAH: Jurnal Pendidikan, 2021)
Using the Problem-Based Learning (PBL) model in elementary school classrooms has been shown to positively impact students' learning outcomes. There are numerous ways in which PBL helps students learn in the primary grades. There is still a paucity of research from reputable national journals on PBL in elementary education for this review. Articles on problem-based learning and the basics of education were pulled from the indexed national education journal Sinta Indonesia as part of the literature review method. Based on the criteria, 16 articles were chosen from the results list. The literature review results show that the PBL model can have a positive impact in general. The research that has been done has improved and had an effect. Elementary school students have made significant strides in a variety of areas, including behavior, attitude, academic performance, and character traits such as initiative, responsibility, cooperation, and critical thinking. Because of PBL's similarities to early childhood education, it should be considered for inclusion there.